MICROBIOLOGICAL STUDIES ON FINFISHES COLLECTED FROM LOWER ANAICUT, TAMIL NADU, INDIA - BALASUBRAMANIAN, P.; SIVAKAMI, RAMAN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Microbial infections can prove fatal if not treated early besides causing serious economic losses for the aquaculture industry, hence aquaculture biosecurity problems addressing pathogens and diseases should also be given prime focus. Hence the present study was undertaken to analyse the presence of bacterial and fungal pathogens present in the water as well as in the instestinal tracts of the commonly occurring fishes of this system. For the present investigation, the samples were collected from the River Cauvery, Lower Anicut, Thanjavur District, Tamil Nadu. This river has a rich source of fish diversity with a variety of fishes like murrels, cat fish, carps and eels. The details of size and weight of the various fishes analysed in this study and the bacterial load in water as well as the fishes analysed. Water recorded the highest load of bacterial count. Among the various fishes, Channa punctatus recorded the highest bacterial load (38 x 103cfu/ml) followed by Puntius conchonius (36 x 103Cfu/ml) and Mystus vittatus (34 X 103Cfu/ml). The least amount of bacterial load was found in Catla catla (1.2 x 103Cfu/ml). A total of 13 fungal species could be identified in the water samples of the system Among the fishes, C. catla recorded the presence of 8 fungal species in their intestinal tract. On the other hand, C. punctatus recorded the presence of 9 fungal species while C. batrachus recorded the presence of 10 fungal species and M. vittatus and P. conchonius recorded the presence of 11 fungal species each. Thus, on the whole, water recorded maximum number of fungal species followed by M. vittatus and P. conchonius respectively. In M. vittatus, Rhizopus nigricans and Achlya hypogyna were not recorded while in P. conchonius, Alternaria alternata and Achlya prolifera were not recorded. C. catla and L. rohita recorded the least number of fungi (8 each). However in C. catla, A. fumigatus, Penicillium citrinum, R. nigricans, A. prolifera and A. hypogyna were not recorded while in L. rohita, A.fumigatus, A. alternata, Curvularia lunata, A. prolifera and Mycelia sterilia were not recorded. Thus, it appears that each fish had a specific fungi. This could probably be due to the body composition of each fish along with its immunity to resist certain fungi. However, a closer perusal reveals that 4 fungi (Aspergillus niger, Aspergillus flavus, Fusarium oxysporium and Cladosporium herbarum) were common to all fish species. However, the degree of infection of varied from species to species and it appeared to be a reflection of the species composition of water.